Student’s Learning Strategies During Pandemic To Get A High Score On TOEIC Test - Titin Kustini; Afief Fakhruddin (Jurnal Educatio FKIP UNMA, 2023)
TOEIC is one indicator for mastery of English language skills. SMKN 1 Kadipaten and SMKN 1 Majalengka are two vocational schools that get the opportunity for a free TOEIC test from Ministry of Education and Culture. This research was conducted to find out how students' learning strategies in the pandemic dealing with the TOEIC test to achieve high scores related to learning situations during the pandemic. The study was conducted on the12th grade students in two vocational schools. Data were obtained from the distribution of questionnaires to students in the two vocational schools, observations and interviews with English teachers. The most of them said they didn’t prepare specially for the test (61,9%). For learning strategy they used, just prepare by browse and look at TOEIC tutorial video (24,2%), discuss with a friend (11%), and 6,6% said they did the exercise from the sources that teacher shared. Only 1,6% who got guidance from teacher by WhatsApp chat, 4,9% by direct explanation, 0,5% by zoom/google meet. In conclusion, they used learning strategy by self-study. The lack of guidance from the teachers caused their TOEIC test score to be low. This is also correlated with their low awareness of the benefits of taking the TOEC test. They said did the test just for experience (51,9%). To improve test results in the future, it is very necessary to have more intensive guidance from teachers and also to growth motivation so that they have the purpose to get the best results.